The potential use of brewers' spent grain-based substrates as horticultural bio-fertilizers - Bianco, Angela; Melito, Sara; Garau, Matteo; Giannini, Vittoria; Zara, Giacomo; Assandri, Davide; Oufensou, Safa; Coronas, Roberta; Pampuro, Niccolò; Budroni, Marilena (Frontiers in Sustainable Food Systems, 2024)
Introduction Brewers' spent grain (BSG) is the most important by-product of breweries. Currently, the primary method of recycling BSG is through its use in livestock feed production, due to its high fiber content, non-degradable protein, and water-soluble vitamins. Nonetheless, composting, vermicomposting, and biochar production pathways offer promising alternatives for managing this organic byproduct. Methods BSG-based substrates were evaluated as bio-fertilizers for use during the transplantation of Lactuca sativa L. and without additional fertilization at the end of the crop cycle. Biochar (B), vermicompost (V), compost (CP), and compost enriched with a microbial consortium (CPE), each mixed at 2 and 4% with peat, were compared with two control treatments: 100% peat (C1) and peat with ternary chemical fertilizer (C2). The experiment was designed with six replicates, half of which were inoculated with Sclerotinia sclerotiorum mycelium during transplantation to assess the contribution of different substrates to pathogen resistance. Results Overall, it was found that the control treatment C2 was the most effective, yielding the greatest plant height at the seedbed stage and the best results across all parameters at harvest. The V 4%, CP 4%, and CPE 4% treatments showed similar results without significant differences compared to the control. At the end of the seedbed phase, plants treated with CP 4% and CPE 4% exhibited the most substantial root development, with statistically significant differences from all other treatments. Moreover, the CPE 4% treatment demonstrated superior performance, resulting in statistically significant differences (p < 0.05) in the chlorophyll content (α and β) and carotenoid parameters when compared to the control treatment C2. The interaction between the treatment and the pathogen was statistically significant only for the carotenoid content in the CPE 4% treatment and for the flavonoid content in most of the treatments. Discussion The most promising results were obtained at the nursery phase, highlighting the potential use of processed BSG-based substrates as bio-fertilizers. These products provided plants with both a growth substrate and nutrients, effectively contributing to waste recycling and aligning with the principles of a circular economy. Additional studies are required to investigate the potential use of brewer's spent grain as bio-fertilizers in other vegetable crop species.